Access to infrastructure and human well-being: evidence from rural Nepal. Issue 2 (17th February 2018) - Sapkota, Jeet Bahadur
ABSTRACT: This article documents the level of access to infrastructure and assesses its perceived impacts on human well-being in rural Nepal. The study found a more varied level of well-being in less remote communities and determined that the perceived impacts of access to infrastructure on human well-being is higher in more remote areas. Notably, access to roads received the highest priority among respondents, followed by drinking water and irrigation. The methodology and findings of this study have practical implications for rural development in hills and mountains where human settlements are highly dispersed and access is key to human well-being.